EFFECTS OF CRUDE BIRTH RATE ON ECONOMIC GROWTH IN NIGERIA - OGUNBADEJO, HUSSAIN KEHINDE; KANWANYE, HILARY TEMOFEH; ZUBAIR, AISHA ARAMA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
This paper explores Nigeria's crude birth rate relationship with her economic growth based on time-series information spanning 1970 to 2019, sourced from the Nigerian Bureau of Statistics, the Central Bank, the World Bank and other relevant agencies.The variables adopted unit roots and cointegration while the two-stage least squares (2SLS) estimation technique was adopted in the analysis. They were all of order one and the result showed a cointegration among them. The 2SLS results showed significant positive relationships between crude birth rate and per-capita income, while an inverse relationship was found to exist between literacy rate and crude birth rate. Results also showed that literacy rate and total labour participation spurred the per capita income of Nigeria. And the paper concludes that the literacy rate is an important policy instrument that can lower the birth rate and raise per capita income in Nigeria.